2007
DOI: 10.1080/13613320701658431
|View full text |Cite
|
Sign up to set email alerts
|

Uneven playing field or falling standards?: Chinese students' competence in English

Abstract: This paper explores student and teacher perspectives of challenges relating to the levels of competence in English of Chinese students studying overseas from the perspective of critical pedagogy. It draws on two complementary studies undertaken by colleagues at the University of Reading. The first-a research seminar attended by representatives from a wide range of UK universitiespresents the views of teachers and administrators; the second draws on four case studies of the language learning of Chinese postgrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Many of these students have significant difficulties with English academic writing, and these difficulties not only add to tensions in the supervisory relationship (Edwards, Ran, and Li 2007;Strauss and Walton 2005;Strauss, Walton, and Madsen 2003) but contribute significantly to their lack of agency. Students also have to contend with the psychological feeling of language incompetence, which is characterised by Leki (1992, 11) shock' that is perhaps more salient than actual language ability.…”
Section: Eal Students and Academic Writingmentioning
confidence: 97%
“…Many of these students have significant difficulties with English academic writing, and these difficulties not only add to tensions in the supervisory relationship (Edwards, Ran, and Li 2007;Strauss and Walton 2005;Strauss, Walton, and Madsen 2003) but contribute significantly to their lack of agency. Students also have to contend with the psychological feeling of language incompetence, which is characterised by Leki (1992, 11) shock' that is perhaps more salient than actual language ability.…”
Section: Eal Students and Academic Writingmentioning
confidence: 97%
“…The historical development of such programmes in the UK was described by Currie and Knights (2003). However, the attention of researchers has hitherto been focused upon their social adjustment and language competence (Edwards et al 2007;Gu and Maley 2008;Turner 2006).…”
Section: Aims Of the Present Studymentioning
confidence: 99%
“…Many British scholars have investigated and reported the difficulties Chinese students face in their daily and academic life (Cortazzi and Jin, 1997;Edwards and Ran, 2006;Edwards et al, 2007;Liu, 2009;Spencer-Oatey and Xiong, 2006). In these investigations, academic matters such as understanding lectures, adapting study skills and studentteacher relationships have been identified as the biggest source of difficulty for Chinese students.…”
Section: Chinese Students' Experiences Of Humor In Britainmentioning
confidence: 99%